Postoperative morbidity after radical gastric resections - MAMALIGA, Catalina (One Health & Risk Management, 2021)
Introduction. Gastric cancer is one of the most common and deadly neoplasms in the world. Although it’s incidence is declining, it remains still high (according to GLOBOCAN – 11,1:100000 in 2020), with more that 1 million new cases each year. Gastric cancer kills annually more than 700 000 people, reaching the 5th place in the top of cancer-related deaths. The 5 – year life expectancy is only 28%. Although, early diagnosis is difficult, treatment outcomes are favorable and in early – stage cancer surgery plays a key role. Gastric surgery is technically difficult alone, but in oncology it also must respect several principles, which multiplies the intervention-related risks. Material and methods. Review type study. Bibliographic search in PubMed and Google Scholar databases, applying the keywords „gastric cancer”, „lymph-node dissection”, „gastric resection”, „early complications”, „Clavien-Dindo classification” and „late complications”. The full articles published in known journals during the last 5 years as a priority have been selected. Information on gastric resection complication types, diagnosis, classification and treatment was selected and processed, so the final bibliography includes 49 references. Results. Gastric resections are complicated operations which require specific surgical skills and deep knowledge of anatomy not only regarding abdominal organs, but lymph-node stations also. The early – morbidity rate in gastrectomy varies between 13-38% and depends on patient-related factors – comorbidities, age, sex, nutritional status and surgery-related factors – the extent of lymphadenectomy, the type of gastrointestinal reconstruction, the time of intervention, the volume of hemorrhage and surgeon experience. The mortality associated to these interventions is also high and varies between 2-8,5%. The late-morbidity rate varies between 5-10% and alter significantly patients’ lives, determining nutritional disorders, low BMI, cachexia and psychological stress. Several questionnaires-based studies have shown that gastric resections reduce considerably the respondents’ quality of life. Conclusions. The gastric cancer surgery is marked by high early and late morbidity and mortality, therefore choosing between two borders of extended intervention with great risks and uncertain long-term benefits and limited intervention which doesn’t respect the oncological principles might be difficult, so the physician should make a decision which would bring the best benefits and the least risk. Study of post-operative complications is crucial because they have a major impact on intervention results, on the long-term survival and on the quality of life. We need further studies to assess the cost-benefit analysis of implementing screening programs for risk groups in order to detect early-stage gastric cancer, as treatment outcomes are better, and the intervention-related risks are lower.